2008
DOI: 10.1001/archderm.144.7.873
|View full text |Cite
|
Sign up to set email alerts
|

Association of Localized Intravascular Coagulopathy With Venous Malformations

Abstract: To determine which venous malformations (VMs) are at risk for coagulopathy. Venous malformations are slow-flow vascular malformations present at birth, and localized intravascular coagulopathy (LIC) causes pain and thrombosis within a lesion and severe bleeding during surgical procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
257
2
11

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 283 publications
(279 citation statements)
references
References 19 publications
9
257
2
11
Order By: Relevance
“…However, a few patients are at risk of potential aggravation of LIC to DIC with dramatic bleeding during a surgical excision, and marked consumption of platelets, coagulation factors, and fibrinogen. 4 Therefore, measurement of D-dimer levels is mandatory in the management of VMs. 13 Venous malformation is not the only disease that can increase D-dimer levels highly and persistently in otherwise healthy patients, other conditions like glomerulonephritis, chronic rejection of renal allograft, and normal pregnancy may also lead to chronic LIC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a few patients are at risk of potential aggravation of LIC to DIC with dramatic bleeding during a surgical excision, and marked consumption of platelets, coagulation factors, and fibrinogen. 4 Therefore, measurement of D-dimer levels is mandatory in the management of VMs. 13 Venous malformation is not the only disease that can increase D-dimer levels highly and persistently in otherwise healthy patients, other conditions like glomerulonephritis, chronic rejection of renal allograft, and normal pregnancy may also lead to chronic LIC.…”
Section: Resultsmentioning
confidence: 99%
“…Localized intravascular coagulopathy is seen as abnormally high D-dimer in few VMs. 4 Phleboliths are seen only in cases of sporadic VMs. Venous malformations are slow-flow vascular malformations present at birth, and LIC causes pain and thrombosis within a lesion and severe bleeding during surgical procedures.…”
Section: Introductionmentioning
confidence: 99%
“…VM are accompanied by spontaneous thrombosis and thrombolysis (19,20). Coagulation disorders are the result of chronic venous blood stagnation within the large irregular vascular spaces, leading to activation of coagulation cascade reactions following production of thrombin, the conversion of fibrinogen into fibrin, which induces the blood clot formation.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent research Rootman et al [5] have demonstrated that CHs are noninfiltrating, focal venous malformations. They lack hyperplasia, that is, the cell turnover rate is not altered and they grow (when they do it, by an average 10 % per year) owing to phenomena of localized intravascular coagulation (LIC) and subsequent inflammation [6]. Just like other Puig Type I venous malformations, they are (almost) excluded from the general circulation [7].…”
mentioning
confidence: 99%
“…Small, asymptomatic malformations, especially those located intraconally, can be just observed over time. Nonsurgical measures such as low molecular weight heparin could be used to stem episodes of LIC [6].…”
mentioning
confidence: 99%